Nutrient intake and brain biomarkers of Alzheimer's disease in at-risk cognitively normal individuals: a cross-sectional neuroimaging pilot study. Issue 6 (24th June 2014) - Mosconi, Lisa; Murray, John; Davies, Michelle; Williams, Schantel; Pirraglia, Elizabeth; Spector, Nicole; Tsui, Wai H; Li, Yi; Butler, Tracy; Osorio, Ricardo S; Glodzik, Lidia; Vallabhajosula, Shankar; et al.
Abstract : Objective: There is increasing evidence to suggest that diet, one of the most important modifiable environmental factors, may play a role in preventing or delaying cognitive decline and Alzheimer's disease (AD). This study examines the relationship between dietary nutrients and brain biomarkers of AD in cognitively normal individuals (NL) with and without AD risk factors. Design: As part of an ongoing brain imaging study, participants received clinical and laboratory examinations, a neurocognitive test battery, positron emission tomography (PET) with 11 C-Pittsburgh Compound-B (PiB; a measure of amyloid-β (Aβ) load) and 18 F-fluorodeoxyglucose (FDG; a proxy of neuronal activity), and completed semiquantitative food frequency questionnaires. Setting: Research centre affiliated with the Alzheimer's disease Core Center at New York University School of Medicine. Participants: 49 NL individuals (age 25–72 years, 69% women) with dietary information, 11 C-PiB and 18 F-FDG PET scans were examined. Results: Controlling for age and total caloric intake, higher intake of vitamin B12, vitamin D and ω-3 polyunsaturated fatty acid (PUFA) was associated with lower Aβ load in AD regions on PiB-PET, while higher intake of β-carotene and folate was associated with higher glucose metabolism on FDG-PET. β-carotene and folate were associated with reduced glucose metabolism for women, apolipoprotein E epsilon 4 (APOE4) carriers and participants with positive AD family history, but not for their risk-free counterparts. The associations of vitamin B12, vitamin D and ω-3 PUFA with PiB retention were independent of gender, APOE and family history. The identified nutrient combination was associated with higher intake of vegetables, fruit, whole grains, fish and legumes, and lower intake of high-fat dairies, meat and sweets. Conclusions: Our data provide a potential pathophysiological mechanism for epidemiological findings showing that dietary interventions may play a role in the prevention of AD. Longitudinal studies are needed to determine whether there is a direct link between nutrient intake, brain biomarkers and risk of AD.